Ribociclib Inhibits P-gp-Mediated Multidrug Resistance in Human Epidermoid Carcinoma Cells - Zhang, Lei; Ye, Biwei; Lin, Yunfeng; Li, Yi-Dong; Wang, Jing-Quan; Chen, Zhuo; Ping, Feng-Feng; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
The efficacy of cancer chemotherapy can be attenuated or abrogated by multidrug resistance (MDR) in cancer cells. In this study, we determined the effect of the CDK4/6 inhibitor, ribociclib (or LEE011), on P-glycoprotein (P-gp)-mediated MDR in the human epidermoid carcinoma MDR cell line, KB-C2, which is widely used for studying P-gp-mediated MDR in cancers. The incubation of KB-C2 cells with ribociclib (3 - 9 µM) increased the efficacy of colchicine, a substrate for P-gp. The cell expression of P-gp was down-regulated at both translation and transcription levels. Furthermore, ribociclib produced a 3.5-fold increase in the basal activity of P-gp ATPase, and the concentration required to increase basal activity by 50% (EC50) was 0.04 μM. Docking studies indicated that ribociclib interacted with the drug-substrate binding site of P-gp. The short-term and long-term intracellular accumulation of doxorubicin greatly increased in the KB-C2 cells co-cultured with ribociclib, indicating ribociclib inhibited the drug efflux activity of P-gp. The results of our study indicate that LEE011 may be a potential agent for combined therapy of the cancers with P-gp mediated MDR.